In vitro iron bioaccessibility and uptake from orange-fleshed sweet potato (Ipomoea batatas (L.) Lam.) clones grown in Peru - André, C.M.; Burgos, G.; Ziebel, J.; Guignard, C.; Hausman, J.F.; Felde, T. zum (Elsevier, 2018)
Research to evaluate the potential of sweet potato to alleviate iron deficiency in affected human populations in developing countries is scarce. To partly fill this gap, we evaluated the bioaccessibility of iron in six sweet potato clones grown in two Peruvian environments, Satipo and San Ramon, following an in vitro gastro-intestinal digestion procedure. The bioaccessible iron content was clone-dependent and 1.7-fold higher in Satipo (5.15 <my>g/g of fresh weight (FW)) as compared to San Ramon (3.04 <my>g/g of FW). Aspects of iron bioavailability were then investigated using the Caco-2 cell model and ferritin synthesis as a marker, on two sweet potato clones after addition of an extrinsic source of iron to the digestion mixture.Results indicated that clone “CIP-194540.5” was presenting higher bioaccessible iron and lower phenolic contents and showed higher iron uptake as compared to clone “CIP-1055011.1” in both environments (91% vs. 24% in Satipo and 67% vs. 13% in San Ramon, respectively). These iron uptake values are higher than the ones previously reported for potato, which further stresses the use of sweet potato storage roots as part of a healthier diet in developing countries.